Aprovechamiento de residuos lignocelulósicos de la ananas comosus (piña) para la producción de xilitol por hidrólisis enzimática (2017)
This research consisted of an experimental development with a series of consecutive stages for the production of biotechnologically xylitol, initially used pineapple peel residues of the variety MD2, commercially known as pineapple Golden. For the peel selection obtained at each street vending machine, two qualitative requirements were established with reference to the maturation of the pineapple, such as the degree of coloration of the shell; The one in which the yellow coloring covers 51-80% of the surface of the body of the fruit and the appearance of the bracts of this fruit (flat fruit), a selective sampling was carried out after obtaining a sample at each point , Verifying likewise the health of the residues, preventing the action of microorganisms and possible processes of deterioration. A muffle drying, milling and sieving were carried out as physical pretreatments whose purpose is the adequacy and conservation of the residues and later stored by size. To begin the experimentation, it was necessary to perform a sampling technique by quartet, to obtain the analytical sample and representative of all the acquired and selected residues.